Professores de Biologia e ensino de evolução: uma perspectiva comparativa em países com contraste de relação entre Estado e Igreja na América Latina - Heslley Machado Silva (2015)
The conflict between scientific knowledge and religious have risen in several areas worldwide. Among the more sensitive themes in this topic is the teaching of biological evolution, with reverberation in the educational policy field in many countries. It is sustained that the context of the teacher of Biology can influence their views about the biological evolution. In this research was selected Latin - American countries with distinct relations between the State and the Church. Argentina with an official religion, and Brazil formally secular, but relativized, and Uruguai with its secularism consolidated. It was also investigated how the teachers conceive a biological evolution, using as tools the questionnaires of BIOHEAD-CITIZEN, through interviews and analysis of biology Curricula. In the analysis of the questionnaires were used the Barbour categories to the relations between science and religion, Conflict, Independence, Dialogue and Integration. While Argentine and Uruguayan teachers indicated independence between the two fields, the Brazilians chose mainly between the categories of conflict, dialogue and integration. The influence of the kind of religion in the teacher's conceiving proved plausible. The brazilian interviews also showed a distinct pattern of speech, pointing out the religion as a major obstacle to the teaching of evolution; in other countries, there were lots of answers. All Brazilian teachers claimed the existence of conflict in the classroom, something less common in the other two countries. Only Brazilians indicate an internal conflict between scientific knowledge and religious when teaching biological evolution. This conflict helps how to explain the discrepancy between the answers to the questionnaire. Another possible explanation is the loss-making training about the issue. The Argentine and Uruguayan teachers reported that the biological evolution is contemplated without religious interference, unlike half of the Brazilians. The Uruguayan curriculum is more assertive about the subject, while in Argentina and Brazil, the curricula have a common ground, delegating to the states crucial points, therefore allowing distortions. We can conclude that the Brazilian teachers experience have a higher difficulty in the teaching of evolution, particularly in relation to religion, while this issue is far from the reality of the two other countries.